2006
DOI: 10.1086/506256
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Embryonal Subunit of the Acetylcholine Receptor (CHRNG) Cause Lethal and Escobar Variants of Multiple Pterygium Syndrome

Abstract: Multiple pterygium syndromes (MPSs) comprise a group of multiple-congenital-anomaly disorders characterized by webbing (pterygia) of the neck, elbows, and/or knees and joint contractures (arthrogryposis). In addition, a variety of developmental defects (e.g., vertebral anomalies) may occur. MPSs are phenotypically and genetically heterogeneous but are traditionally divided into prenatally lethal and nonlethal (Escobar) types. To elucidate the pathogenesis of MPS, we undertook a genomewide linkage scan of a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(123 citation statements)
references
References 24 publications
4
116
0
3
Order By: Relevance
“…The common findings in these patients were prenatally detected restriction of movements; craniofacial dysmorphisms, including down-slanting palpebral fissures, low-set ears, and micrognathia; and multiple contractures of the limbs ( Figure 2B). The distribution of CHRNG mutations detected in our study is shown in Figure 2, C and D. Two of the identified CHRNG mutations have not been reported, while the other mutations, including the recurrent mutation, have been reported previously in MPS patients (20,36). In 1 of 3 patients with the same homozygous CHRNG mutation (BAB5611), we additionally identified another homozygous deleterious mutation in a different arthrogryposis gene, ERCC2 (c.1775G>A; p.Arg592His) (Figure 2A Other identified variants in known genes are delineated in Tables 1 and 2.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The common findings in these patients were prenatally detected restriction of movements; craniofacial dysmorphisms, including down-slanting palpebral fissures, low-set ears, and micrognathia; and multiple contractures of the limbs ( Figure 2B). The distribution of CHRNG mutations detected in our study is shown in Figure 2, C and D. Two of the identified CHRNG mutations have not been reported, while the other mutations, including the recurrent mutation, have been reported previously in MPS patients (20,36). In 1 of 3 patients with the same homozygous CHRNG mutation (BAB5611), we additionally identified another homozygous deleterious mutation in a different arthrogryposis gene, ERCC2 (c.1775G>A; p.Arg592His) (Figure 2A Other identified variants in known genes are delineated in Tables 1 and 2.…”
Section: Discussionsupporting
confidence: 46%
“…Although most of the MPS cases were reported with a pattern of autosomal-recessive inheritance (15), autosomal-dominant transmission was also observed in a few cases (16)(17)(18). While homozygous and compound heterozygous mutations of CHRNG (19,20) were associated with both lethal and nonlethal types of MPS, mutations of CHRND (21) and CHRNA1 (21) are also responsible for lethal MPS. Recently, homozygous mutations in RYR1 (22) and autosomal-dominant inheritance with MYH3 mutations were reported in MPS patients (23).…”
Section: Resultsmentioning
confidence: 99%
“…Expressing human AChR γ-subunit in ε -/-mice rescues the lethality of the ε-subunit gene deletion, but the rescued mice continue to display AChR deficiency and develop phenotypes similar to human congenital myasthenic syndromes (Cossins et al, 2004). Furthermore, mutations in human AChR γ-subunit gene (CHRNGHuman Gene Nomenclature Database) cause severe prenatal myasthenia (Escobar or multiple pterygium syndrome) (Hoffmann et al, 2006;Morgan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, the γ-subunit KO is lethal (6), and in humans, mutations in the cholinergic receptor, nicotinic, gamma (CHRNG) gene that encodes for γ-subunit are associated with lethal forms of multiple pterygium and Escobar syndromes (7)(8)(9).…”
mentioning
confidence: 99%